Electric-field-driven translocation of ssDNA through hydrophobic nanopores - Haynes, T; Smith, I; Wallace, E; Trick, J; Sansom, M; Khalid, S (American Chemical Society, 2018)
The accurate sequencing of DNA using nanopores requires control over the speed of DNA translocation through the pores and also of the DNA conformation. Our studies show that ssDNA translocates through hourglass-shaped pores with hydrophobic constriction regions when an electric field is applied. The constriction provides a barrier to translocation and thereby slows down DNA movement through the pore compared with pores without the constriction. We show that ssDNA moves through these hydrophobic pores in an extended conformation and therefore does not form undesirable secondary structures that may affect the accuracy of partial current blockages for DNA sequencing.